2020
DOI: 10.21203/rs.3.rs-31631/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Current Transition Management of Adolescents and Young Adults with Allergy and Asthma: A European Survey.

Abstract: Background: Transition from parent-delivered to self-management is a vulnerable time for adolescents and young adults (AYA) with allergy and asthma. There is currently no European guideline available for healthcare professionals (HCPs) on transition of these patients and local/national protocols are also mostly lacking. Methods: European HCPs working with AYA with allergy and asthma were invited to complete an online survey assessing challenges of working with these patients, current transition practices and a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Based on the recent survey, we know that there is a lack of adult allergy services, as well as availability of HCP with a specific expertise (psychologists and dieticians) in many European countries 2 . There is a need for an individualized and coordinated transition process between the AYA, family and medical services to ensure the best outcomes.…”
Section: Discussion Gaps In the Evidence And Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the recent survey, we know that there is a lack of adult allergy services, as well as availability of HCP with a specific expertise (psychologists and dieticians) in many European countries 2 . There is a need for an individualized and coordinated transition process between the AYA, family and medical services to ensure the best outcomes.…”
Section: Discussion Gaps In the Evidence And Future Perspectivesmentioning
confidence: 99%
“…The recommendations could be implemented at a patient, family and society level, through education, training, resources and service delivery design 94 . Based on the recent survey, HCP find managing AYA to be a challenge 2 . Therefore, it would be helpful to implement training in the generic transition process in undergraduate and postgraduate training programmes (Table 7).…”
Section: Discussion Gaps In the Evidence And Future Perspectivesmentioning
confidence: 99%
“…The 2019 survey by the European Academy of Allergy and Clinical Immunology (EAACI) adolescents and young adult task force showed that healthcare professionals find managing this age group to be a challenge [ submitted , Ref. 2]. Unmet needs were also identified, for example most services do not have an established approach and related resources to effectively support this age group.…”
Section: Figurementioning
confidence: 99%
“…That the developmental changes of adolescence are still occurring in the early 20s explains why we should focus on this wider 11‐ to 25‐year adolescents and young adult age group 7 . With paediatric patients being transferred into adult services around 16‐18 years of age, 2 plans for supporting effective self‐management in the adult healthcare service need to take into account these ongoing major lifestyle changes and their potential impact. This is particularly so with the patient moving to college, university or work.…”
Section: Figurementioning
confidence: 99%
“…The Taskforce has also conducted a Europe‐wide survey with healthcare professionals to assess challenges of working with AYA and their current transition practices. With over 1000 responses from 41 countries, the survey revealed that awareness and in particular resources for transition processes for AYA were badly lacking 8 . On the basis of this work, the Taskforce has published EAACI guidelines for the effective transition of AYA with asthma and allergic conditions, 9 which add some condition‐specific elements to already published generic transition documents such as the NICE guidelines (https://www.nice.org.uk/guidance/ng43, last accessed 7 September 2020).…”
mentioning
confidence: 99%